2008
DOI: 10.1103/physrevlett.100.056806
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Binding Energy and Bohr Radius of a Single Hydrogenic Defect in a Semiconductor Quantum Well

Abstract: Low-temperature scanning tunneling spectroscopy under ultrahigh vacuum was used to study donor point defects located at the epitaxial surface of an In(0.53)Ga(0.47)As quantum well. The electronic local density of states was measured with nanoscale resolution in the vicinity of single defects. In this way, both the binding energy and the Bohr radius of the defects could be determined. The binding energy and the Bohr radius were found to be functions of the quantum well thickness, in quantitative agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Earlier STM and density-functional theory (DFT) work revealed the stability of this reconstruction and showed that the MBE-grown surface exhibits native In adatoms residing on the vacancy sites [11]. STS measurements [13] further indicated that the In adatom acts as a donor supplying one electron to the conduction band, similar to the charge state found for native cation adatoms on epitaxial In 0:53 Ga 0:47 Asð111ÞA [14]. The STM topograph in Fig.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Earlier STM and density-functional theory (DFT) work revealed the stability of this reconstruction and showed that the MBE-grown surface exhibits native In adatoms residing on the vacancy sites [11]. STS measurements [13] further indicated that the In adatom acts as a donor supplying one electron to the conduction band, similar to the charge state found for native cation adatoms on epitaxial In 0:53 Ga 0:47 Asð111ÞA [14]. The STM topograph in Fig.…”
supporting
confidence: 53%
“…We attribute this observation to the emergence of the first excited In 5 ''molecular orbital'' (MO) state having a nodal plane at the center atom position. In the range of higher bias (>0:5 V for In 5 ), we find that the excited MO type states are superimposed by a different type of surface states most likely deriving from adatominduced localization effects [14].…”
mentioning
confidence: 78%
“…In addition to the investigation of the electronic structure of point defects or impurities (Perraud et al, 2008;Wijnheijmer et al, 2009) and the carrier dynamics between their bound states and the semiconductor bands, STM also provides access to the charge state of the defect as a function of the sample voltage. For example, the Si dangling bond, which corresponds to a nonbonded sp 3 -hybrid orbital, pointing outward of the surface, is known to exist in different charge states.…”
Section: Electrical Properties Of Single Point Defectsmentioning
confidence: 99%
“…As a typical example of the properties of dopants, the ionization energies of dopants in nanoscale structures have been intensively studied. [26][27][28][29][30] For dopants to exist in nanoscale structures, the doping concentration is required to be sufficiently high. For understanding carrier transport in highly doped nanoscale semiconductors, conductance in one-dimensional doped semiconductors as a function of the gate voltage has been widely explored in terms of localized disordered systems in the 1980s.…”
Section: Introductionmentioning
confidence: 99%